Influence of baseline modified Rheumatic Disease Comorbidity Index (mRDCI) on drug survival and effectiveness of biological treatment in patients affected with Rheumatoid arthritis, Spondyloarthritis and Psoriatic arthritis in real‐world settings. (23rd August 2018) - Iannone, Florenzo; Salaffi, Fausto; Fornaro, Marco; Di Carlo, Marco; Gentileschi, Stefano; Cantarini, Luca; Lopalco, Giuseppe
Abstract: Aim: To assess the impact of baseline modified Rheumatic Disease Comorbidity Index ( m RDCI) a simple comorbidity count, on overall survival of treatments with biological drugs in patients affected with Rheumatoid Arthritis (RA), Spondyloarthritis (SpA) and Psoriatic Arthritis (PsA) in real‐world settings. Methods: Patients (nr. 635) with RA (nr. 214), SpA (nr. 213) and PsA (nr. 208) starting a first biological drug were retrospectively analysed. mRDCI was scored at baseline, and disease characteristics were recorded at entry and at last observation. Drug retention was analysed using Kaplan‐Meier curves. Cox regression models were used to estimate the association of baseline mRDCI with drug discontinuation and clinical outcomes, the achievement of clinical remission based on 28 joint‐Disease Activity Score (DAS28) <2.6 for RA and PsA, and on Ankylosing Spondylitis‐C‐reactive protein Disease Activity Score (ASDAS‐CRP) <1.3 for SpA. Results: Baseline mRDCI significantly correlated with the number of biological drug switches ( rho 0.26). Persistence on biologic therapy was significantly higher in patients with mRDCI=0 (96.4%), than in those with mRDCI ≥2 (83.9%). Patients without comorbidities showed significantly higher drug survival rate in PsA ( P  = 0.0001) or SpA ( P  = 0.02), but not in RA. mRDCI was also found to be a predictor of definitive drug discontinuation (HR: 1.53) and of failure to achieve remission in RA (HR: 0.66) or PsA (HR: 0.77), and in SpA (HR: 0.43). Conclusions: This study provided evidence that baseline m RDCI negatively impacts the persistence on biologic treatments and clinical outcomes in patients with RA, SpA and PsA in real‐life settings.